Red de Pocket Parks, intervenciones urbanas de consolidación, desde ocupaciones verdes en el PIT S-9 del cantón Baños. - Guaypatín Herrera, Doménica Samantha (2024)
In the urban context, Pocket Parks become important elements in the design and planning of public space. These small green spaces offer significant benefits in terms of quality of life and urban consolidation. Therefore, the implementation of Pocket Parks in Cantón Baños is presented as a necessary intervention, since the absence of green areas in PIT S-9 has been identified, which negatively affects the quality of life of its residents. For the execution of this project, a study of theoretical sources is being carried out to provide a guide to the history and implementation process of Pocket Parks. In addition, a quantitative research based on the AEUB methodology, which involves the collection of data through data collection sheets, is being carried out. At the same time, a macro, meso and micro level analysis is developed to understand the current state of the canton. In order to obtain reliable information for decision making through the results obtained. As a product of this project, the design of a network of Pocket Parks is proposed in order to reverse the deficient indicators identified in the PIT S-9 of Baños de Agua Santa Canton. This network not only seeks to improve the quality of life of the inhabitants, but also to revitalize the urban environment and promote urban consolidation.